STRATEGI PEMASARAN JASA - Juhana , Dudung (Majalah Bisnis & IPTEK, 2021)
Services are all actions or activities that can be offered by one party to the other is intangible and does not cause any ownership. Characteristics of services, namely intangible or invisible. Inseparable, among the services provided by the service provider. Then varied, in this case is the standard value of a service to the customers is different. And the last is easily lost, because the service only when the transaction process between the service provider and the customer takes place. After that services will be lost, quality of service or service is the level of the gap between the expectations or desires of customers with the perception or the performance they have felt. Keywords: strategy; marketing services